Dosis de fertilización inorgánica y orgánica su efecto en las características agronómicas y rendimiento de forraje Tithonia diversifolia (Hemsl.) A. Gray. "botón de oro" en Loreto, Perú- 2020 - Mozombite Inuma, Aldo (2022)
The research work was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Vacunos Project in the Zungarococha Farm, entitled “INORGANIC AND ORGANIC FERTILIZATION DOSE ITS EFFECT ON AGRONOMIC CHARACTERISTICS AND FORAGE YIELD (Tithonia diversifolia Hemsl.) A. Gray. "BOTON DE ORO" IN LORETO, PERU- 2020 ". The evaluations were carried out 60 days after sowing with plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 170 m2. With a Random Complete Block Design (DBCA), with five treatments and four repetitions, the treatments under study were: T0 (0 tons / ha), T1 (10 tons / ha), T2 (20 tons / ha) and T3 (30 tons / ha) and T4 (40 tons / ha), obtaining the following results: With the treatment T2 (20 tons / ha) it was possible to increase the average plant height (m), green matter (kg / m2) , dry matter (kg / m2),% of plant cover and green matter in Kg / ha. In this sense, it was shown that at least one of the doses of inorganic and organic fertilization favorably influenced the agronomic characteristics and the yield of the forage Tithonia diversifolia. According to what was found in this work, the dose of 20 tons / ha of chicken manure positively influences the research.